CPA examination reviewer : auditing theory - Roque, Gerardo S. (Recto, Manila : GIC Enterprises & Co. Inc., 2014)
This reviewer is a compilation of multiple choice questions that are based on current pronouncements of the auditing and assurance standards council (AASC)
1. An introduction to assurance, auditing, and related services -- 2. The accountancy profession -- 3. The CPAs professional responsibilities -- 4. The financial statements audit -- 5. Risk assessments and internal internal control -- 6. Auditing in a computer information systems -- 7. Audit objectives, procedures, evidence and documentation -- 8. Audit sampling -- 9. Completing the audit and post audit responsibilities -- 10. The auditors report on financial statements -- 11. Other reporting responsibilities -- 12. Practice examinations.
Includes bibliographical references.
Keywords: AUDITING